PMO-202 Use of the Blatchford score to identify low-risk upper gastrointestinal bleeds. (28th May 2012) - Disney, B R; Watson, R; Blann, A; Lip, G; Tselepis, C; Anderson, M
Abstract : Introduction: Acute upper gastrointestinal bleeding is a medical emergency associated with a significant health burden and risk of mortality. A significant proportion of patients are admitted to hospital unnecessarily for endoscopy following presentation with acute upper gastrointestinal bleeding. The Blatchford score can be used to identify patients with low-risk gastrointestinal bleeds suitable for discharge and outpatient endoscopy. However, some debate remains regarding what level of Blatchford score can be considered low-risk. The aim of this study was to assess the need for intervention in patients presenting with upper gastrointestinal bleeding based upon the admission Blatchford score. Methods: All patients admitted with acute upper gastrointestinal bleeding to Sandwell and West Birmingham Hospitals NHS Trust from 1 January 2009 to 31 December 2009 were included in the study. Results: Overall, 470 patients with acute upper gastrointestinal bleeding were admitted during the study period. Of these 67.2% were male and 32.8% female. The mean age of patients was 64.0±18.8 years. The most common diagnosis was peptic ulcer disease, which was found in 34.5% of patients. A Blatchford score of 0 accounted for 6.0% of patients (n=28) and 14.7% (n=69) had a Blatchford score ≤2. Of the patients admitted with a Blatchford score ≤2 none required intervention (transfusion, endoscopic therapy or surgery) and there were no deaths. These patients were significantly younger than patients with a Blatchford score >2 (mean age 44.1±17.5 years for a Blatchford score ≤2 vs 67.4±18.8 years for a Blatchford score >2). Conclusion: Patients with acute upper gastrointestinal bleeding with a Blatchford score ≤2 did not require inpatient intervention and can be considered for early discharge from hospital with outpatient endoscopy. This strategy identified 14.7% of patients in our population that were unnecessarily admitted. Using a Blatchford score of ≤2 may help to significantly reduce hospital admissions. Competing interests: None Declared.